2014
DOI: 10.1007/s11010-014-2093-4
|View full text |Cite
|
Sign up to set email alerts
|

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma

Abstract: The Fork head box C1 (FOXC1) gene is overexpressed in multiple malignant tumors and is functionally correlated with tumor progression. However, its’ role in oral squamous cell carcinoma (OSCC) is still unclear. Recent studies have revealed that many long non-coding RNA (lncRNAs) cooperate with adjacent coding genes and form a functional “lncRNA-mRNA pair”. In this study, we report a new lncRNA FOXC1 upstream transcript (FOXCUT) that was remarkably overexpressed in 23 OSCC patients, as was the adjacent FOXC1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 22 publications
5
56
0
Order By: Relevance
“…FOXCUT is a novel lncRNA (NR_125804.1) located on chromosome 6p25 and upstream of the FOXC1 promoter. Previous studies showed that the FOXCUT-FOXC1 regulatory network is associated with tumorigenesis and cancer progression in oral squamous cell carcinoma and breast cancer; 12,13 however, the function of the FOXCUT-FOXC1 pair in NPC has not been described. In this study, we investigated the expression levels and clinicopathological characteristics of the FOXCUT-FOXC1 pair in NPC and explored the role of FOXCUT in cell proliferation and migration associated with NPC to evaluate its efficacy as a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…FOXCUT is a novel lncRNA (NR_125804.1) located on chromosome 6p25 and upstream of the FOXC1 promoter. Previous studies showed that the FOXCUT-FOXC1 regulatory network is associated with tumorigenesis and cancer progression in oral squamous cell carcinoma and breast cancer; 12,13 however, the function of the FOXCUT-FOXC1 pair in NPC has not been described. In this study, we investigated the expression levels and clinicopathological characteristics of the FOXCUT-FOXC1 pair in NPC and explored the role of FOXCUT in cell proliferation and migration associated with NPC to evaluate its efficacy as a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported metastasis‐associated lung adenocarcinoma transcript 1 (MALAT‐1) was overexpressed and MEG3 was attenuated in TSCCs (Fang et al., ). The long non‐coding RNA FOXCUT (FOXC1 promoter upstream transcript) and its neighboring gene FOXC1 were upregulated in OSCC, and knockdown of either of them inhibited cell proliferation, colony formation, migration, and invasion (Kong et al., ). LncRNA SOX2 overlapping transcript (SOX2OT) has two splice variants (SOX2OT‐S1 and SOX2OT‐S2) which were co‐upregulated with master regulators of pluripotency, SOX2 and OCT4, in ESCC tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, our result is contradictory to studies of FOXC1 in nasopharyngeal cancers, as studies show that reduced FOXC1 in nasopharyngeal cancers cells are associated with a decrease in MMP9. 24,25 These differences are likely due to the use of different cell lines and tissues of origin used in these studies, again suggesting a tissue-specific role of FOXC1 in disease pathogenesis. This is the first study illustrating a link between FOXC1 and the prostaglandin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%